Neuroimaging: what neuroradiological features distinguish abusive from non-abusive head trauma? A systematic review. Issue 12 (30th September 2011) - Kemp, A M; Jaspan, T; Griffiths, J; Stoodley, N; Mann, M K; Tempest, V; Maguire, S A
Abstract : Objectives: To identify the evidence base behind the neuroradiological features that differentiate abusive head trauma (AHT) from non-abusive head trauma (nAHT). Design: Systematic review. Setting: Literature search of 14 databases, websites, textbooks, conference abstracts and references (1970–February 2010). Studies had two independent reviews (three if disputed) and critical appraisal. Patients: Primary comparative studies of children <11 years old hospitalised with AHT and nAHT diagnosed on CT or MRI. Main outcome measures: Neuroradiological features that differentiated AHT from nAHT. Results: 21 studies of children predominantly <3 years old were analysed. Subdural haemorrhages (SDH) were significantly associated with AHT (OR 8.2, 95% CI 6.1 to 11). Subarachnoid haemorrhages were seen equally in AHT and nAHT and extradural haemorrhages (EDH) were significantly associated with nAHT (OR for AHT 0.1, 95% CI 0.07 to 0.18). Multiple (OR 6, 95% CI 2.5 to 14.4), interhemispheric (OR 7.9, 95% CI 4.7 to 13), convexity (OR 4.9, 95% CI 1.3 to 19.4) and posterior fossa haemorrhages (OR 2.5, 95% CI 1 to 6) were associated with AHT. Hypoxic-ischaemic injury (HII) (OR 3.7, 95% CI 1.4 to 10) and cerebral oedema (OR 2.2, 95% CI 1.0 to 4.5) were significantly associated with AHT, while focal parenchymal injury was not a discriminatory feature. SDH of low attenuation were more common in AHT than in nAHT. Conclusion: Multiple SDH over the convexity, interhemispheric haemorrhages, posterior fossa SDH, HII and cerebral oedema are significantly associated with AHT and should be considered together with clinical features when identifying the condition.